Grounding Al-Farabi's Musical Philosophy Through Stecu's Song: Integration of Art, Spirituality, and Islamic Education (International Journal of Education and Literature, 2024)
This study examines the SteCu Song (Aesthetic and Cultural Studies by Civitas) as a form of aesthetic movement that combines art, music, and Islamic philosophy. Through a historical-hermeneutic approach, the main question asked is: how can the SteCu Song be read as an aesthetic practice that is in line with the principles of Islamic music philosophy, especially as stated in the Book of al-Musiqa al-Kabir by al-Farabi? This study aims to examine the relationship between contemporary musical expression in the SteCu Song with aesthetic and ethical concepts in classical Islamic philosophy. The method used is descriptive qualitative with text analysis and musical practice, as well as a theoretical approach that refers to al-Farabi's thoughts on music as a means of forming the soul and morals. The main theoretical framework in this study is the theory of harmony of the soul and the educational function of music according to al-Farabi, which is combined with the theory of art as a medium of social meaning. The results of the study show that SteCu Songs are not only a form of artistic expression, but also contain educational and spiritual dimensions that are in line with al-Farabi's idea of ​​music as a means of purifying the soul (tazkiyat al-nafs). These songs present moral reflections, values ​​of togetherness, and calls for goodness, thus placing musical art in the context of progressive cultural da'wah. This study recommends the development of similar musical works as a medium for learning Islamic philosophy that is applicable and contextual.